The effect of upper body anaerobic pre-loading on 2000-m ergometer-rowing performance in college level male rowers - Purge, P.; Hofmann, P.; Merisaar, R.; Mueller, A.; Tschakert, G.; Mäestu, J.; Jürimäe, J. (Journal of Sports Science & Medicine, 2017)
Elevated blood lactate has been shown to influence subsequent anaerobic exercise due to an inhibition of glycolysis. The aim of the present study was therefore to investigate the influence of a short and high-intensity anaerobic arm crank pre-load exercise (HIE) added to a low-intensity warm-up on cardio-respiratory and metabolic responses on a subsequent all out rowing exercise. Nine well-trained college level male rowers (24.6 ± 7.1 yrs; 1.87 ± 0.07 m; 88.9 ± 9.8 kg; 18.5 ± 3.7% body fat) volunteered to participate in the study. The subjects performed a maximal 2000-m rowing ergometer performance tests (MPT) twice. One MPT was preceded by a normal low intensity warm-up (MPTlow), while another one was performed with the additional inclusion of the HIE protocol (MPThigh). Overall rowing performance in the MPTlow was significantly faster (p = 0.004) by 3.7 ± 2.8 sec compared to the MPThigh condition (401.7 ± 23.0 s v. 405.4 ± 23.3 s) but the reduction in speed was found only for the first 1000-m (p = 0.017). Net La increase from rest to the end of the MPTlow was 11.9 ± 2.3 mmol·l-1 which was significantly higher (p = 0.0001) compared to the MPThigh condition (6.3 ± 1.8 mmol·l-1). Carbon dioxide output was significantly lower in the second (p = 0.041), third (p = 0.009), fourth (p = 0.036) and fifth (p = 0.028) 250-m split in the MPThigh compared to the MPTlow test. In conclusion, HIE upper-body anaerobic pre-load added to a standard low intensity warm-up protocol decreased anaerobic performance only in the early stages of the MPThigh but the latter part was unaffected. The inhibition of glycolysis in the first minute of the workout might allow a different race strategy, which needs to be investigated in further studies. Key Points